Case Report: Partial Uniparental Disomy Unmasks a Novel Recessive Mutation in the LYST Gene in a Patient With a Severe Phenotype of Chédiak-Higashi Syndrome - Boluda-Navarro, Mireia; Ibáñez, Mariam; Liquori, Alessandro; Franco-Jarava, Clara; Martínez-Gallo, Mónica; Rodríguez-Vega, Héctor; Teresa, Jaijo; Carreras, Carmen; Such, Esperanza; Zúñiga, Ángel; Colobran, Roger; Cervera, José Vicente (Frontiers in Immunology, 2021)
Chédiak-Higashi syndrome (CHS) is a rare autosomal recessive (AR) immune disorder that has usually been associated to missense, nonsense or indels mutations in the LYST gene. In this study, we describe for the first time the case of a CHS patient carrying a homozygous mutation in the LYST gene inherited as a result of a partial uniparental isodisomy (UPiD) of maternal origin. Sanger sequencing of the LYST cDNA and single nucleotide polymorphism (SNP)-arrays were performed to identify the causative mutation and to explain the molecular mechanism of inheritance, respectively. Partial-UPiD leads to a copy neutral loss of heterozygosity (CN-LOH) of the telomeric region of chromosome 1 (1q41q44), unmasking the potential effect of the mutation detected. The mutation (c.8380dupT) is an insertion located in exon 32 of the LYST gene resulting in a premature stop codon and leading to the loss of all the conserved domains at the C-terminal of the LYST protein. This would account for the severe phenotype observed. We also reviewed the only two previously reported cases of CHS as a result of a uniparental disomy. In this study, we show that the combination of different strategies, including the use of SNP-arrays, is pivotal to fine-tune the diagnosis of rare AR disorders, such as CHS. Moreover, this case highlights the relevance of uniparental disomy as a potential mechanism of CHS expression in non-consanguineous families.